PENGEMBANGAN MEDIA POP-UP BOOK RANTAI MAKANAN PADA PEMBELAJARAN IPAS DI SD MUHAMMADIYAH 3 SURABAYA - Sokran, Dinda Iftitach; Holy Ichda Wahyuni; Meirza Nanda Faradita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
ABSTRACT Pop-up Book is a three-dimensional media designed to stimulate children's creativity while expanding their knowledge, making it easier to understand the representation of the shape of an object. The purpose of this study is to assess the validity, effectiveness, and practicality of the Food Chain Pop-up Book media that combines texts, songs, quizzes, and interactive visuals in the learning of Natural and Social Sciences (IPAS) in grade V of SD Muhammadiyah 3 Surabaya. The ADDIE (Analyze, Design, Develop, Implement, and Evaluate) model is used as a development approach in this study. The research sample consisted of 24 students in grade V and had validation sheets, questionnaires, and final tests. The results of the study prove that the percentage of validation of material experts is 90%, and the percentage of validation of media experts is 98% with a total of 94% of the total validation is included in the very valid criteria. The student response sheet showed a percentage of 91%, included in the very valid criteria, while the teacher response sheet reached a percentage of 100% in the very valid category. The percentage of field trial results through posttest is 89%, which is also very valid. The results of the instrument prove that the Food Chain Pop-Up Book media used in IPAS learning is very valid and suitable for use in grade V elementary school learning. Keywords: Pop-up Book, Food Chain, Learning Media ABSTRAK Pop-up Book merupakan media tiga dimensi yang dirancang guna merangsang kreativitas anak sekaligus memperluas ilmu mereka, sehingga memudahkan dalam memahami representasi bentuk suatu objek. Penelitian ini bertujuan untuk menilai validitas, efektivitas, dan kepraktisan media Pop-up Book Rantai Makanan yang menggabungkan teks, lagu, kuis, dan visual interaktif dalam pembelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) di kelas V SD Muhammadiyah 3 Surabaya. Model ADDIE (Analyze, Design, Develop, Implement, and Evaluate) digunakan sebagai pendekatan pengembangan dalam penelitian ini. Sample penelitian terdiri dari 24 siswa kelas V dan memiliki lembar validasi, angket, dan tes akhir. Hasil penelitian membuktikan persentase validasi ahli materi sebesar 90%, dan persentase validasi ahli media sebesar 98% dengan total keseluruhan validasi mencapai 94% termasuk dalam kriteria sangat valid. Lembar respon siswa menunjukkan persentase sebesar 91%, masuk dalam kriteria sangat valid, sedangkan lembar respon guru mencapai persentase 100% dalam kategori sangat valid. Persentase hasil uji coba lapangan melalui postest adalah 89%, yang juga tergolong sangat valid. Hasil instrument membuktikan bahwa media Pop-Up Book Rantai Makanan yang digunakan dalam pembelajaran IPAS sangat valid dan layak digunakan dalam pembelajaran kelas V Sekolah Dasar. Kata Kunci: Pop-up Book, Rantai Makanan, Media Pembelajaran